Медицина против... медицины: частные расследования / М. Я. Жолондз - Жолондз Марк Яковлевич (Лань, 1996)
Экземпляры: аб. (1997) / Инвентарный номер: 39767 / Цена: / Сис.шифр: 54.1 / Авт.знак: Ж 79 / ГРНТИ: 76.29.29 / ББК: 54.101